Facilitating information-seeking activity in instructional videos: The combined effects of micro- and macroscaffolding. (September 2017) - Cojean, Salomé; Jamet, Eric
Abstract: With the development of e-learning, and more specifically MOOCs, searching for information in videos is becoming a key activity in education. Many studies have focused on learning in video-based environments, but to our knowledge, they have left aside the question of search tasks. We hypothesized that information-seeking activity can be improved by adapting features of the learning environment, more particularly by providing micro- and/or macroscaffolding. To test this hypothesis, we assessed the effects of presentation during a search activity in a video-based environment. A total of 80 students were divided into four groups, then exposed to a video 1) with or without a table of contents (macroscaffolding), and 2) with or without markers in the timeline (microscaffolding). Results showed that micro- and macroscaffolding both have positive effects on search outcomes, but also that they need to be used in combination to improve search times. One possible interpretation is that, in the absence of scaffolding, users have to compensate by constructing their own mental representations of the video segmentation, which is cognitively very costly and highly time consuming. Highlights: We studied the effects of scaffolding level on searching for information in videos. Micro and macro levels have specific effects on navigation and semantic searches. Combining the two levels of scaffolding facilitates the search activity. Results are discussed in terms of mental model building with or without scaffolding.